“Mártir da pureza, heroína da castidade”: a construção da santidade de Benigna Cardoso em Santana do Cariri/CE-(1941-2022) - SILVA, Tatiana Olegário da (2023)
The work aims to analyze the process of building a “feminine sanctity” between the 20th and 21st centuries, Where the idea of chastity, honor and femininity are in constant change/transformation. We propose to carry out this analysis based on the story of Benigna Cardoso da Silva, a Young Woman who, on October 24, 1941, When carrying out a common activity, going to get water from a well for her home, was raped and murdered by a classmate, Raul Alves Ribeiro, in the city of Santana do Cariri/CE. At the time, Benigna was just 13 years old and Raul was 17. The murder aroused sensivity in the population and, throughout Benigna’s history, there has been time, admirers, thus becoming for her devotees a “saint” and “admirers complete “hero of chastity”. This phenomenon gave rise, from the year 2004 onwards, to the pilgrimage of pilgrims to the place of the murder. With the passing, the devotion went to more sincere people of the notoriety and encourage devotion, publicizing the cult, inserting symbols in the history of lite and death Benigna and initianting the beatifications is used, having the incluence of institutions, the Church and the public power as the axis of the problematization of thi devotion, questioning how They built the image of Benigna transform – a in the canonical and oficial blessed molds. To better understand these aspects, we resort to the concepts and contributions of some outhors thtat will be essential in this research, Roger Chartier (1990), Michel de Foucault (2012), Michel de Certeau (2000) among other authors that help us to have a better theoretical foundation.